Fatty liver-index, systemic inflammation and cardiovascular mortality: results from the LURIC study - Wissel, Stephanie; Scharnagl, Hubert; Kleber, Marcus E.; Delgado Gonzales de Kleber, Graciela; Moissl-Blanke, Angela P.; Krämer, Bernhard; März, Winfried (Atherosclerosis, 2025)
Background and aims - The Fatty Liver Index (FLI) has emerged as an indicator of metabolic dysfunction and has been related to cardiovascular outcomes. This study aims to investigate if the association between FLI and cardiovascular mortality is modified by systemic inflammation. - Methods - The study population consisted of 3316 participants (mean age 63 years, 30,3 % female) of the Ludwigshafen Risk and Cardiovascular Health (LURIC) study. The FLI was calculated using triglycerides, BMI, waist circumference, and gamma-glutamyl transferase (GGT). Systemic inflammatory markers (hsCRP and IL-6) were measured with immunoturbidimetric and ELISA assays. The outcome of interest was cardiovascular mortality. Cox proportional hazard analyses accounting for confounding variables were used for statistical analyses. - Results - During a median follow-up of 9.9 years, 603 cardiovascular deaths occurred. Individuals in the highest compared to the lowest FLI tertile were at an increased risk of cardiovascular death (HR 1.39, 95 % CI 1.02-1.89). This association was significantly modified by elevated hsCRP (≥2 mg/L, HR 1.58, 95 % CI 1.10-2.26) and IL-6 (≥3.2 ng/L, (HR 1.93, 95 %CI 1.36-2.74). - Conclusion - The Fatty Liver Index is not associated with cardiovascular mortality. However, this relationship is modified by systemic inflammation. These results indicate that liver steatosis is particularly relevant in presence of systemic inflammation which suggests that risk assessment in individuals with steatosis needs to consider both metabolic and inflammatory markers.
Online verfügbar: 31. Oktober 2025, Artikelversion: 11. November 2025
Gesehen am 12.11.2025